Masificación de las fake news en la plataforma facebook año 2024 - Puzma Granda, Eliane Karps (2025)
Fake news is news that contains false, distorted, or unverified information, often disguised as real news, which tends to generate chaos and distrust in society. This research aims to analyze the massification of fake news on the Facebook platform, case study: El Diario de Riobamba, January to June 2024. The methodological application employed a qualitative approach, focusing on the variable of content analysis of the massification of fake news on the Facebook platform in 2024. The study examined a sample of 78 publications to identify the main factors influencing the perception of news published on digital platforms as false. On the other hand, three interviews were applied to address the variable of the Facebook Platform: case study the Diario de Riobamba, in which integrates Diego Moncayo director of theDiario de Riobamba, Pablo Escandón Montenegro professor of communication area of the Universidad Andina Simón Bolívar, and, José Rivera expert in communication and digital marketing. Thus, it was concluded that the massification of fake news corresponds to a problem that must be addressed to prevent users from falling into deception and viralizing information that is not verified or contrasted. For this reason, the massification of fake news has a negative impact on users, as the alteration of information leads to a distrust of what the media disseminates.